1999
DOI: 10.1097/00126334-199908150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Incident HIV Infection in a High-Risk, Homosexual, Male Cohort in Rio de Janeiro, Brazil

Abstract: An HIV seroincidence study was conducted to identify a high-risk population for HIV prevention trials. Inclusion criteria were male gender, homosexual behavior, age between 18 and 50 years, and negative HIV serostatus; 862 study subjects were screened and 753 were enrolled and observed during follow-up for a mean of 1.5 years. In this population, 34 people had HIV seroconversions for an overall annual seroincidence of 3.1% (95% confidence interval [CI], 2.1%-4.1%). Among study subjects <20 years old, annual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…This result is similar to other cohort studies with MSM 3 , 13 , 15 , which indicates that retention rate is higher after the initial period of the study and remains stable over time. It is possible that the connection and commitment to the study were not well established in the first years of participation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to other cohort studies with MSM 3 , 13 , 15 , which indicates that retention rate is higher after the initial period of the study and remains stable over time. It is possible that the connection and commitment to the study were not well established in the first years of participation.…”
Section: Discussionsupporting
confidence: 90%
“…In the Multicenter AIDS Cohort Study (MACS), the retention rate was 88.5% in 9.5 years of follow-up 3 . The Brazilian Praça Onze cohort study monitored seronegative MSM and reported retention rates of 97%, 91%, and 88% at six, 12, and 18 months of follow-up 13 , respectively. An American study with Latino population of homosexuals/bisexuals and transgender persons reported retention rates of 83% and 80% in three and six months of follow-up, respectively 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Although not quite significant, there was a trend towards greater willingness to participate in rectal microbicide trials among men at higher risk of HIV infection (P 5 0.056) when only men who had definite opinions on participation were included. This association between an increased risk of HIV infection and willingness to participate in HIV prevention trials has been consistently identified in MSM who are potential trial participants, both in Australia [37] and in other countries [34,35,[38][39][40][41]. The combination of high HIV incidence and increased willingness to participate in trials further indicates the suitability of such a population for prevention trials.…”
Section: Discussionmentioning
confidence: 82%
“…Other risk factors for higher HIV incidence were identified from other published sources and examined within the HIM cohort. These included number of sexual partners in the past 6 months [32,33,34], alcohol consumption [33], previous hepatitis B virus (HBV) infection [35] and injecting drug use [33]. For each risk factor, the HIV incidence was calculated as the number of HIV seroconversions divided by the total PY of follow-up for participants who reported/experienced that risk factor.…”
Section: Factors Associated With An Hiv Incidence Of 2 Per 100 Pymentioning
confidence: 99%
“…The HIV incidence among pregnant women did not show a decline; the rate was 0.72% in 1999, 1.11% in 2000, and 0.59% in 2002 (Saphonn, 2003). Although the incidence study showed declining trends of HIV incidence among the high-risk groups, one should be aware that HIV incidence among these groups is still high compared with the high-risk groups in other countries (Harrison et al, 1999;Vanichseni et al, 2001) (Figure 5). …”
Section: Hiv Incidencementioning
confidence: 97%